2009
DOI: 10.2967/jnmt.109.062059
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Perfusion in the Lateral Wall of the Left Ventricle in PET/CT Studies with 13N-Ammonia: Evaluation in Healthy Adults

Abstract: This study evaluated the causes of the frequently observed decreased myocardial perfusion in the lateral wall of the left ventricle in PET/CT studies with 13 N-ammonia in healthy adults. Methods: Thirty-two adults who were undergoing PET/CT of the heart with 13 N-ammonia as part of a study of the effects of posttraumatic stress disorder in American Indians were included. Participants who had evidence of heart disease by a physician-administered questionnaire or by pharmacologic stress during the myocardial per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…Lautamäki et al also performed a 2D PET/CT study and found that misregistrations of 10 and 14 mm resulted in up to a 19% and 225% change in relative uptake in the septum and the lateral wall, respectively, whereas a 5-mm misregistration had no noticeable effect on uptake (8). Our results are in line with the results of those 2D PET/CT studies (4)(5)(6)(7)(8), indicating that the influence of misregistration on altered uptake is similar between 3D PET/CT and 2D PET/CT.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Lautamäki et al also performed a 2D PET/CT study and found that misregistrations of 10 and 14 mm resulted in up to a 19% and 225% change in relative uptake in the septum and the lateral wall, respectively, whereas a 5-mm misregistration had no noticeable effect on uptake (8). Our results are in line with the results of those 2D PET/CT studies (4)(5)(6)(7)(8), indicating that the influence of misregistration on altered uptake is similar between 3D PET/CT and 2D PET/CT.…”
Section: Discussionsupporting
confidence: 90%
“…Previous 2D PET/CT studies demonstrated that artifactual defects occurred predominantly in the LV anterior and lateral walls (4,5,7), which have the largest surface area in common with the lung. When there is a substantial overlap between lung and heart, the marked difference in attenuation factors between lung and heart is considered a main reason for the observed changes in measured uptake (6).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations